2007
DOI: 10.1111/j.1365-2958.2007.05924.x
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi adhesins identified using in vivo phage display

Abstract: SummaryBorrelia burgdorferi, the agent of Lyme disease, disseminates from the site of deposition by Ixodes ticks to cause systemic infection. Dissemination occurs through the circulation and through tissue matrices, but the B. burgdorferi molecules that mediate interactions with the endothelium in vivo have not yet been identified. In vivo selection of filamentous phage expressing B. burgdorferi protein fragments on the phage surface identified several new candidate adhesins, and verified the activity of one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 65 publications
(109 reference statements)
2
108
0
9
Order By: Relevance
“…Surprisingly, the role of OspC in mammalian infection can be partially replaced by the overexpression of other B. burgdorferi lipoproteins, although the mechanism of this phenomenon has not been investigated (62). Curiously, though, this work revealed a critical role for OspC in the colonization of some of the tissues examined, particularly in the heart, which is consistent with previously published results from two other laboratories (2,28). A specific function for OspC in infection is supported by the recent demonstration that a site-directed change of one residue in a putative ligandbinding pocket rendered the bacteria noninfectious in the mouse model of infection (17).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Surprisingly, the role of OspC in mammalian infection can be partially replaced by the overexpression of other B. burgdorferi lipoproteins, although the mechanism of this phenomenon has not been investigated (62). Curiously, though, this work revealed a critical role for OspC in the colonization of some of the tissues examined, particularly in the heart, which is consistent with previously published results from two other laboratories (2,28). A specific function for OspC in infection is supported by the recent demonstration that a site-directed change of one residue in a putative ligandbinding pocket rendered the bacteria noninfectious in the mouse model of infection (17).…”
supporting
confidence: 81%
“…Purified maltosebinding protein (MBP)-␤-galactosidase (␤gal) and MBP-OspC were described previously (2). Purified proteins were tested at 1 and 10 g/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Research on the borrelial Erp outer surface proteins has revealed multiple properties associated with mammalian infection (2,3,11,12,34,37,40,45,59). Given what is known of their functions, it is not surprising that B. burgdorferi Erp proteins are produced during mammalian infection but repressed during colonization of tick vectors (10,31,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Erp proteins are located in the bacterial outer membrane and are exposed to the external environment (25,32,41). Known functions of Erp proteins include binding of host plasmin(ogen), laminin, and the complement regulators factor H and factor H-related proteins 1, 2, and 5 (2,3,11,12,34,37,40,45,59). These functions indicate roles for Erp proteins in host adherence, dissemination, and resistance to the alternative pathway of complement-mediated killing.…”
mentioning
confidence: 99%
“…Additionally, bba66 is expressed during persistent mouse infection, suggestive of a maintenance function for B. burgdorferi in a reservoir host or as a needed component to colonize host tissues (14,17). Studies by Anguita et al suggested that bba66 may play a role in Lyme arthritis and carditis as assessed in the C3H/HeN mouse model (21), and Antonara et al found evidence for BBA66 adhesion to murine heart tissue by phage display assay (22). Like other genes in this complex, notably bba64, bba66 is controlled by the Rrp2-RpoN-RpoS global regulation pathway, which regulates a subset of genes both in the tick transition portion of the enzootic cycle and during mammalian infection (7,13,16,(23)(24)(25)(26).…”
mentioning
confidence: 99%